VASTRAVIKAS: UNRAVELING INDIA’S SUSTAINABLE GARMENT LEGACY - Soni, Ritika; Agrawal Srivastava, Neelam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The clothing and textile industry, a cornerstone of India’s rich heritage, is shifting towards sustainable practices by emphasizing reducing, reusing, and recycling materials. This approach ensures that waste decomposes naturally, promoting sustainability. The retail sector in India has grown significantly, evolving from a seller-driven to a buyer-driven market. Historically, India’s retailing started with barter systems, exchanging goods of similar value without money, which played a vital role in the economy and offered solutions to modern cash flow issues. This study examines the recycling practices involving clothes collected by hawkers. Survey results show that urban respondents understand recycling as creating new items from old ones. Hawkers gather used garments, sort, inspect, clean, and then produce useful recycled products. These recycled garments are often bought by middle-class families at affordable prices for their housemaids. To promote sustainable practices in the textile industry, several strategies are recommended. Organizing workshops and training sessions on upcycling can help individuals repurpose old clothing creatively. Establishing community repair centers or providing resources for basic clothing repair techniques can emphasize the importance of repairing and modifying garments. Educational campaigns and community events can promote clothing donations, preserve cultural heritage, and reduce waste. Supporting sustainable textiles involves encouraging local artisans, weavers, and the textile industry, and urging designers to incorporate traditional techniques and fabrics. Awareness campaigns through social media and community events can educate people about the traditional Indian model of garment reuse, further promoting sustainability in the textile industry.